Demonetisation and black money - Rammanohar Reddy, C. (Orient blackswan, 2019)
This book takes a close look at the various facets of the demonetisation story. What was the rationale for Demonetisation 2016? Can it stamp out black money as promised? Were there other options, which would have avoided causing immense grief to countless Indians? What next after demonetization? The book also explores the drive to digitalization of payments which post-demonetisation has emerged as an important agenda of the government.